Conversion of broadband UV-visible light to near infrared emission by Ca14Zn6Al10O35: Mn4+, Nd3+/Yb3+. Issue 9 (19th January 2016) - Gao, Xuejun; Xia, Wenbin; Chen, Tiejin; Yang, Xiaoliang; Jin, Xiangliang; Xiao, Siguo
Abstract : Efficient Ca14 Zn6 Al10 O35 : Mn 4+, Nd 3+ /Yb 3+ spectral conversion materials have been prepared by a sol–gel method. Abstract : Efficient Ca14 Zn6 Al10 O35 : Mn 4+, Nd 3+ /Yb 3+ spectral conversion materials have been prepared by a sol–gel method. The Ca14 Zn6 Al10 O35 : Mn 4+, Nd 3+ /Yb 3+ materials can efficiently shift the short-wavelength sunlight in 250–550 nm spectral regions into near infrared emission which matches the higher sensitivity region of Si-based solar cells. The maximal energy transfer efficiency is 76.0% and 80.4% in Mn 4+, Nd 3+ and Mn 4+, Yb 3+ co-doped samples when excited at 460 nm, respectively. A dipole–dipole interaction is responsible for the energy transfer sensitization processes from Mn 4+ to Nd 3+ /Yb 3+ ions, which has been confirmed by Dexter's theory and the Yokota–Tanimoto model.